2009
DOI: 10.1007/s11104-009-0013-2
|View full text |Cite
|
Sign up to set email alerts
|

Rhizosphere fauna: the functional and structural diversity of intimate interactions of soil fauna with plant roots

Abstract: For decades, the term "rhizosphere fauna" has been used as a synonym to denote agricultural pests among root herbivores, mainly nematodes and insect larvae. We want to break with this constrictive view, since the connection between plants and rhizosphere fauna is far more complex than simply that of resource and consumer. For example, plant roots have been shown to be neither defenceless victims of root feeders, nor passive recipients of nutrients, but instead play a much more active role in defending themselv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
124
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(140 citation statements)
references
References 212 publications
2
124
0
6
Order By: Relevance
“…Moreover, earthworms likely possess a unique capability of neutralising plant polyphenols that otherwise strongly decrease decomposition rates of fresh plant litter (Liebeke et al, 2015). Micro-and mesofauna excrete ammonium or dissolved organic carbon (Filser, 2002;Fox et al, 2006;Osler and Sommerkorn, 2007) and affect the quantity of microbial metabolites (Bonkowski et al, 2009). Gut passage, defecation, and excretion, together with bioturbation by macro-and mesofauna, facilitate humification and decomposition, also altering nutrient stoichiometry (Bohlen et al, 2004).…”
Section: Molecular Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, earthworms likely possess a unique capability of neutralising plant polyphenols that otherwise strongly decrease decomposition rates of fresh plant litter (Liebeke et al, 2015). Micro-and mesofauna excrete ammonium or dissolved organic carbon (Filser, 2002;Fox et al, 2006;Osler and Sommerkorn, 2007) and affect the quantity of microbial metabolites (Bonkowski et al, 2009). Gut passage, defecation, and excretion, together with bioturbation by macro-and mesofauna, facilitate humification and decomposition, also altering nutrient stoichiometry (Bohlen et al, 2004).…”
Section: Molecular Structurementioning
confidence: 99%
“…Roots preferably grow in existing soil cavities (Jiménez and Lal, 2006), mostly formed by soil fauna (Wilkinson et al, 2009). Both burrowing and non-burrowing soil animals have a strong impact on root growth, allocation, length and density (Brown et al, 1994;Bonkowski et al, 2009;Arnone and Zaller, 2014). Animal grazing of root bacteria and mycorrhiza affects their activity and community composition, and animal excreta are enriched in micronutrients and selectively affect plant nutrition (Brown, 1995;Filser, 2002;Brussaard et al, 2007).…”
Section: Rootsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the different occurrence of underground objects in the gallery systems of these species is likely due to their different foraging preferences. Fibrous roots are a carbon source for many soil-inhabiting invertebrates, such as earthworms (Curry and Schmidt 2007), nematodes, and many insect larvae (Bonkowski et al 2009). Fibrous roots provide an interface between plants and soil, and the transportation of nutrients and energy occurs on the surface of these roots (Lavelle and Spain 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In this research, it was found that the pattern of changing biomass in root energy channels followed the pattern of changes in root biomass. A possible explanation on the pattern form biomass of root energy channels may be related to the dynamics of root defense mechanism against soil fauna feeding on root (Bonkowsky et al, 2009). Biomass in energy channels of fungi, bacteria or saprophagous macro-arthropods between ages of cocoa plantation was not significantly different ( Figure 3B, 3C, and 3D).…”
Section: Biomass Of Energy Channelmentioning
confidence: 93%